An algebra problem by Pandu Christian

Algebra Level pending

If e^(2x)+e^x=6

x = ?

ln 2 or ln (-3) ln 2 and ln (-3) None of these ln (-3) ln 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sriharsha Ch
Apr 5, 2016

e 2 x e^{2x} + e x e^{x} = 6 = 6

( e x ) 2 (e^{x})^{2} + e x e^{x} = 6 = 6

e x e^{x} = y = y

y 2 y^{2} + y = 6 + y = 6

y 2 + y 6 = 0 y^{2} + y - 6 = 0

( y 2 ) ( y + 3 ) = 0 (y-2)(y+3) = 0

y 2 = 0 y-2=0 o r or y + 3 = 0 y+3=0

y = 2 y =2 o r or y = 3 y = -3

e x = 2 e^{x} =2 o r or e x = 3 e^{x} = -3

e x = 2 e^{x} = 2

x = l n ( 2 ) x = ln(2)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...